An overview profile and entrepreneurial orientation among Malaysian Indian ethnic entrepreneurs - Perumal, Selvan; Husin, Zolkafli; Othman, Abdul Rahim; Yusr, Maha Mohammed
Entrepreneurship discipline continues to grow and attract the interest of different sectors of society.It gained attention in the various discipline namely management, economics, sociology, and psychology.Therefore, this study aims to investigate an overview of profile of Malaysian Indian ethnic entrepreneurs’ and the level of entrepreneurial orientation.The paper reports and analyses the findings of 201 questionnaires which were collected from selected state in Malaysia such as Selangor, Kuala Lumpur, Perak, Pinang and Kedah. The paper illustrates an overview entrepreneurial profile among Malaysian Indian ethnic entrepreneurs. Furthermore, the result shows that the entrepreneurial orientation level among Malaysian Indian ethnic entrepreneurs is at moderate level.Discussion and implication of this study introduced in the last section on this paper.